Key concepts in drugs and society - Coomber, Ross (London : SAGE, 2013)
"Insightful and illuminating, this book successfully discusses drugs in social contexts. In an elegant manner, the authors bring together their different theoretical and practical backgrounds, offering a comprehensive and interdisciplinary introduction that opens up a wide scientific understanding moving beyond cultural myths and presuppositions. This is an invaluable reference source for students on criminology, sociology and social sciences programmes, as well as drug service practitioners such as drug workers, social workers and specialist nurses"--Publisher's website.
Types of drugs and patterns of use. What Is a drug/medicine? ; Prevalence and trends in illicit drug use ; Why do people take drugs? ; Addiction ; Legal drugs : alcohol and tobacco ; Polydrug use/polysubstance use ; Common illicit drugs ; Typologies of drug use : use-misuse-abuse and problematic-recreational use ; Binge-drinking ; Raves and circuit parties ; Dance drugs/club drugs ; Cross-cultural and traditional drug use ; Gender, ethnicity and social class ; Normalisation. -- Drug effects. Drug effects : drug, set and setting ; Medical marijuana and other therapeutic uses of illicit drugs ; Prescribed and over-the-counter (OTC) drugs ; Novel psychoactive substances ; The gateway hypothesis/stepping stone theory ; Drug-related violence ; Drugs and crime ; Drug risks and health harms ; Injecting drug use ; HIV/AIDS and other blood-borne viruses. -- Drug policy, treatment and perceptions of the drug problem. Drug treatment and quasi-compulsory treatment ; Harm reduction ; Substitute prescribing ; The new recovery approach ; Prevention : primary, secondary and tertiary ; International drug control history/prohibition ; Drugs in sport ; Drug scares and moral panics ; Drug dealers ; Drug markets : difference and diversity ; Drug trafficking ; Crop eradication, crop substitution and legal cultivation ; War on drugs ; Drug testing in schools and workplaces ; Drug courts ; Decriminalisation, legalisation and legal regulation ; Liberalisation.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Psychotropic drugs -- Social aspects; Drug abuse; Electronic books